The Illocutionary Acts Analysis by The Main Character and Its Application in ELT - Wenny purlita dewi; Andrian Nuriza Johan; Zulia Chasanah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2021)
This research deals with Illocutionary Acts Found in Before I Fall movie and Its Application in teaching speaking to eleventh grade students of senior high school. The aims of this research are (1) to find out the types of illocutionary act made by the main character of Before I Fall movie. (2) to describe the application of illocutionary acts found in Before I Fall movie in teaching speaking to eleventh grade students of senior high school. This research belongs to descriptive qualitative research. The data are form Illocutionary acts found in made by main character in Before I Fall movie. It was collected by finding the movie, watching the movie, downloading the script, reading the script, then collecting illocutionary acts utterances of the main character in the movie. After the data collected, the researcher analyzed the data based on the types. The result shows that there are 5 types of illocutionary act found in made by main character in Before I Fall movie. Those are 97 utterances of assertives (32.11%), 112 utterances of directives (37.08%), 5 utterances of commisives (1.65%), 75 utterances of expressives (24.83%), and 11 utterances of declaratives (3.64%). The application of illocutionary acts found in the main character of Before I Fall movie using movie as the method to improve speaking skills of Senior High School learners, so that students will be more interested in learning English.